Performing Non-sexism via Degendering Phoric Forms in English: The Gap between Rules and Practice as Observed in the 9th Edition of Oxford Advanced Learner's Dictionary of Current English - Mulamba, Nshindi-Germain; Tshimanga, Francis Ngoyi Crequi (Lexikos, 2020)
Non-sexism is one of the outstanding and obvious proofs of how social and cultural changes are taken into account in the English language. However, it is still a usage problem for natives and learners alike. This paper uses the degendering of phoric elements as an illustration of efforts in the 9th edition of Oxford Advanced Learner's Dictionary of Current English (OALD9) to capture and express social and cultural changes in the English language. It also attempts to point out some mismatches between rules and actual practice in this enterprise. Finally, it intends to show how the dictionary may act as an ideological tool, imposing, sustaining, highlighting, and perpetuating some points of view to the detriment of others. In practice, the use of more than one structure to achieve non-sexism makes fluency difficult and writing cumbersome.